Everyday Alchemy [detail]. - Hagman, Kristina. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: What have you touched today? What is your relationship with your body? These are only a few of the questions that occupy my mind. I believe that art has the power not only to publicize, but also to redeem some of the negative, objectionable, and destructive factors we encounter in our current world. Art has the power to inspire change.